2001
DOI: 10.1136/oem.58.3.172
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum concentrations of hexachlorobenzene and polychlorobiphenyls with thyroid hormone and liver enzymes in a sample of the general population

Abstract: Objectives-Hexachlorobenzene (HCB) is a highly lipophilic organochlorine compound of widespread environmental occurrence, that accumulates in the biological system. It aVects the porphyrine metabolism, thyroid hormones, and the liver function in animals. Although HCB is one of the most common organochlorine compound in humans, little investigation on its health eVects has been done. Polychlorobiphenyls (PCBs) are also widespread toxic environmental contaminants. The aim of the present study was to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 40 publications
4
40
1
Order By: Relevance
“…Consistent with our results was a recent Canadian study of 149 pregnant women found a significant inverse relationship between low, environmental levels of HCB, PCB 153 and ΣPCBs in plasma and total T 3 , but no associations with free T 4 and TSH (Takser et al 2005). Likewise, inverse associations between PCBs and T 3 levels were also previously observed in the wives of Swedish fishermen (Hagmar et al 2001b) and in German schoolchildren (Osius et al 1999), while another study among Dutch women reported an inverse association with T 3 that was also accompanied by an inverse association with T 4 and a positive association with TSH (Sala et al 2001). Other studies have reported an inverse association between PCBs, and T 4 and/or a positive association between PCBs and TSH, with no association between PCBs and total T 3 (Schell et al 2004;Hagmar 2003;Persky et al 2001;Emmett et al 1988), while another reported no associations between PCBs and thyroid hormones among 160 neonates from North Carolina from 1978 to 1982 (Longnecker et al 2000).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Consistent with our results was a recent Canadian study of 149 pregnant women found a significant inverse relationship between low, environmental levels of HCB, PCB 153 and ΣPCBs in plasma and total T 3 , but no associations with free T 4 and TSH (Takser et al 2005). Likewise, inverse associations between PCBs and T 3 levels were also previously observed in the wives of Swedish fishermen (Hagmar et al 2001b) and in German schoolchildren (Osius et al 1999), while another study among Dutch women reported an inverse association with T 3 that was also accompanied by an inverse association with T 4 and a positive association with TSH (Sala et al 2001). Other studies have reported an inverse association between PCBs, and T 4 and/or a positive association between PCBs and TSH, with no association between PCBs and total T 3 (Schell et al 2004;Hagmar 2003;Persky et al 2001;Emmett et al 1988), while another reported no associations between PCBs and thyroid hormones among 160 neonates from North Carolina from 1978 to 1982 (Longnecker et al 2000).…”
Section: Discussionmentioning
confidence: 81%
“…A study among 608 adults in Spain living near an organochlorine factory that produced HCB found a significant inverse association between serum HCB levels and total T 4 (Sala et al 2001). Total T 3 levels were not measured in the study.…”
Section: Discussionmentioning
confidence: 99%
“…These relationships are surprising but could nevertheless be explained, at least partly, through the relation between plasma organochlorine concentration and lowered plasmafree thyroxine and total thyroxine levels that have been reported in several human studies. [79][80][81] In this regard, an increase in plasma organochlorine concentration during body weight loss was shown to be inversely correlated with changes in tri-iodothyronine (T 3 ) serum concentration 61 and skeletal muscles enzymes activity. 82 Therefore, it suggests that an increase in plasma organochlorine concentration could partly account for the adaptive decrease in thermogenesis during body weight loss, possibly through a deleterious action on thyroid hormone status.…”
Section: Organochlorines: Obesogen Pollutants?mentioning
confidence: 99%
“…However, few studies also demonstrated positive correlation between PCB exposure and TSH (Osius et al, 1999;Schell et al, 2004). By contrast, other studies found no association between PCBs and thyroid secretion (Bloom et al, 2003;Hagmar et al, 2001b;Sala et al, 2001). …”
Section: Polychlorinated Biphenylsmentioning
confidence: 94%